Integrating narrative assessments in medical education by overcoming the existing challenges - Saurabh R. Shrivastava; Prateek S. Bobhate; Ankit K. Badge; Yugeshwari R. Tiwade (Wolters Kluwer Medknow Publications, 2024)
Narrative assessments in medical education have a broad scope and they extend way beyond the boundaries and limitations of traditional grading methods. Acknowledging the merits of narrative assessments in the making of a complete healthcare professional, every institution should aim to structurally introduce these forms of qualitative assessments within their set-ups. Although narrative assessments offer multiple merits, we cannot ignore the presence of the challenges that are linked with them and there is an immense need to address these potential challenges, and we will essentially require thoughtful planning, regular training of teachers, and consistent efforts to refine the process of narrative assessments. In conclusion, in the field of medical education, narrative assessment has significant scope and merits to offer to facilitate the growth of medical students. However, we must be systematic in our approach to integrate these assessments in a meaningful manner and take specific measures to overcome the associated challenges.